The National Library of Norway, Oslo Division: Is it Possible to Make a 1913-Building Accessible for the Library User of 2005? - Nilsen, Sissel (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
National Libraries are mostly regarded as important national institutions, but very few people outside the school and academic circles believe that there can be anything of interest for them inside such an institution.